2006
DOI: 10.1254/jphs.fp0060837
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Emotional Behavior of Mice in the Hole-Board Test After Olfactory Bulbectomy

Abstract: Abstract. The most consistent behavioral change caused by olfactory bulbectomy (OBX) is a hyperemotional response to novel environmental stimuli. The aim of this study was to characterize the emotional behavior of OBX mice using the hole-board test. After the olfactory bulbs were lesioned, sham and OBX mice were housed in single cages for 14 days. The number of head-dips in the hole-board test in single-housed OBX mice was significantly greater than that in single-housed sham mice. The head-dipping behaviors i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(15 citation statements)
references
References 35 publications
1
13
0
1
Order By: Relevance
“…This evidence may be associated with reduced neurogenesis in depression (Atanasova et al, 2008;Negoias et al, 2010). Whereas temporary peripheral anosmia (inducible by zinc sulfate) does not cause behavioral changes (Cain, 1974;Calcagnetti et al, 1996), the destruction of the olfactory sensory receptors does not promote depressive symptoms, and only definitive structural injuries caused behavioral changes (Saitoh et al, 2006), authors argue that the OB model can also be used as a model of neurodegeneration Douma et al, 2012), since bulbectomy causes definitive interruption of neural connections present between the olfactory bulbs and other regions of the brain, particularly the olfactory-limbic circuit (Jesberger and Richardson, 1988).…”
Section: Discussionmentioning
confidence: 98%
“…This evidence may be associated with reduced neurogenesis in depression (Atanasova et al, 2008;Negoias et al, 2010). Whereas temporary peripheral anosmia (inducible by zinc sulfate) does not cause behavioral changes (Cain, 1974;Calcagnetti et al, 1996), the destruction of the olfactory sensory receptors does not promote depressive symptoms, and only definitive structural injuries caused behavioral changes (Saitoh et al, 2006), authors argue that the OB model can also be used as a model of neurodegeneration Douma et al, 2012), since bulbectomy causes definitive interruption of neural connections present between the olfactory bulbs and other regions of the brain, particularly the olfactory-limbic circuit (Jesberger and Richardson, 1988).…”
Section: Discussionmentioning
confidence: 98%
“…Similarly, OBX rats exhibited hyperemotional responses to given stimuli and a decrease in the time spent in the open arm of a plus-maze; these behavioral changes were reduced by subchronic treatment with the antidepressant desipramine for 7 days (Saitoh et al 2003). Thus, it was suggested that the evaluation of hyperemotional behaviors and the performance on a plus-maze in OBX rats may provide a suitable model for evaluating antidepressants (Yamaguchi et al 2002;Saitoh et al 2003Saitoh et al , 2006.…”
Section: Introductionmentioning
confidence: 99%
“…Hole-board apparatus was constructed and experiments conducted as described previously (Saitoh et al, 2006). Rat pups were randomly divided into two groups of 12 animals each.…”
Section: Hole-board Testmentioning
confidence: 99%